EVALUATIVE PATTERNS IN THE OFFICIAL DISCOURSE OF HUMAN RIGHTS IN CHILE: GIVING VALUE TO THE PAST AND BUILDING HISTORICAL MEMORIES IN SOCIET - Oteíza Silva, Teresa (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2009)
This paper analyzes certain patterns of voice realization of the Chilean National Truth and Reconciliation Commission of 1991, established after the end of the military dictatorship (1973-1990). In this official document, produced and promoted by the Chilean Government, the authors strive to present themselves as powerless to judge society or to explain historical events. However, they propose evaluations (evoked and inscribed) of relevant sectors of society, offer an interpretation of history, and specifically, give explanation for the “military intervention” and the possible causes for the severe human rights violations during the dictatorship. Informed by the complementary theoretical approaches of SFL and CDA, I focus on Appraisal analysis (White 2000, 2003; Martin 1997, 2003, 2004; Martin & Rose 2003; Martin & White 2005) and a transitivity analysis of mental and verbal projections in the discourse, as tools for a more flexible and detailed exploration of the use of evaluation resources. This analysis allows us to create a systemic network of the patterns of grammatical and lexical resources used by the Commission to generate mitigation and self/others representation in the discourse. This linguistic analysis, inserted in a social practice, also offers a complementary understanding of the subjectivities found in the field of oral history, specifically in the study of testimonies that account for different and contradictory memories of the recent Chilean past (Stern 2006)